OPTIMALISASI MINAT BELAJAR ANTROPOLOGI MATERI KEARIFAN LOKAL KELAS XII IBB SMA NEGERI 1 BANGIL PADA PEMBELAJARAN DARING MELALUI TEKNIK MENULIS 3M - Puspita, Siska Clara (CV Sintesia, 2024)
This research aims to optimization of interest in learning of students learning in online learning through the 3M technique in local wisdom materials. This study is a class action study with the research subjects of grade XII students IBB SMAN 1 Bangil as many as 76 people. This research was conducted 2 cycles, each cycle consisting of 2 meetings. At each meeting consists of 4 stages namely planning, implementation, observation and reflection. Data collection techniques used include interviews and observations. Based on the results of the study, in cycle I obtained an average student learning activity of 65.63% with enough categories. while in cycle II, the average learning activity of students is 79.69% with a high category. Thus, from cycle I and cycle II there was a 14.06% increase in student activity. thus it can be concluded that through the 3M technique can increase the active learning of grade XII students of SMAn 1 Bangil towards Anthropology lessons, especially local wisdom materials in online learning during the covid-19 pandemic.